Nodular malignant melanoma of maxillary gingivae: A rare presentation and a proposed clinical classification of oral malignant melanoma - Jigna S Shah; Himali A Shah; Yogesh Rathva (Wolters Kluwer Medknow Publications, 2021)
Malignant melanoma arises from melanocytic cells. Oral mucosal melanoma is a rare malignancy with the tendency to metastasize and locally invade tissues more readily than other malignant tumors of the oral cavity. Here, a very rare entity of the pigmented nodular variety of the oral malignant melanoma of maxillary buccopalatal gingiva with regional lymph node involvement and distant metastasis to the lungs is reported. A new proposed clinical classification of oral malignant melanoma is explained. Early detection is very important for a better prognosis.